The Impact of Complex Estimates of IFRS-9 on The Proportion of Key Audit Matters (KAM) Disclosures: Evidence from Jordanian Capital Market - Esraa Esam Alharasis (Asian Academy of Management Journal of Accounting and Finance, 2024)
This study seeks to provide fresh empirical evidence on the way complex IFRS-9 estimations affect Key Audit Matters (KAM) disclosure in Jordan, an impoverished nation. A robust year-industry fixed-effects OLS regression model has been employed to test the developed hypotheses over the period from 2017 to 2022. The investigation showed a substantial statistical relationship between each IFRS-9 complex estimate category (proxied by financial assets held for trade, sale, or maturity) and KAM proportions. The results concurred with nations that IFRS-9 caused capital market uncertainty. To reduce information asymmetry, auditors provide a large number of KAM in their reports to evaluate and appraise complicated estimations. This research may be utilised to set a financial reporting and disclosure policy for unfavourable scenarios. This study updates policymakers and standard-setters on the impact of ISA-701's KAM disclosure requirement. KAM research is helpful for evaluating confidence interval disclosures, external audits, and KAM disclosures' utility following IFRS implementation. Thus, regulatory agencies, standard-setters, stakeholders, and audit report consumers interested in KAM disclosures and ISA-701 implementation in developing nations could gain from this research. The findings may motivate academia to use similar data to other emerging nations to better understand how reporting KAMs influences audit methods. To author knowledge, this is one of the first empirical research to examine the influence of post-IFRS-9 audit processes and the first to refer to its correlation with KAM disclosures. This study is the first to evidence on the impact of IFRS-complex estimations on KAM proportions. How auditors handle investor protection after IFRS introduction and its extended reporting obligations in underdeveloped economies have received little attention. This study examines audit activity under a weak legal framework, unlike other auditing studies, which are highly regulated.